POST-INDUSTRIALIZATION AS THE MOST IMPORTANT TREND OF MODERN PROCESSES IN THE WORLD ECONOMY - Akbarova , Mohinur Farxod qizi (Educational Research in Universal Sciences, 2023)
Post-industrialization is one of the most important trends in modern processes in the global economy. This process has significant impacts on labor force structure, innovation, global trade and sustainable development.